The Impact of Carbon Emission Trading System on ESG of Agricultural Enterprises: Evidence from 24 Listed Agricultural Companies in China - Shen, Chen (Transactions on Economics, Business and Management Research, 2024)
With China’s dual carbon goals of carbon peaking and carbon neutrality, the carbon emission trading system will play a crucial role. In addition, agriculture, which is closely linked to carbon emissions, is a foundational industry in China. It is worth paying attention to how it responds to carbon emission trading policies. This study uses data from agricultural listed enterprises from 2009 to 2022, and employs the Difference-in-Differences (DID) method and the intermediary effect model. The evidence suggests that the the carbon emission trading system will significantly improve the the ESG evaluation of agricultural enterprises. Furthermore, green management innovation, green total factor productivity, and CSR information disclosure quality of enterprises will act as intermediaries. The study calls for the government to accelerate the establishment of a national carbon trading market, improve reward and penalty systems, and evaluation frameworks for green innovation in agricultural enterprises. It also emphasizes the need to strengthen pre-subsidies for small-scale enterprises, encourage environmental literacy training for management personnel in agricultural enterprises, intensify green innovation efforts, and establish relevant department assessments of corporate social responsibility.